2019
DOI: 10.3389/fcell.2019.00289
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of Circular RNAs Mediated ceRNA Regulation in Porcine Embryonic Muscle Development

Abstract: Many circular RNAs (circRNAs) have been discovered in various tissues and cell types in pig. However, the temporal expression pattern of circRNAs during porcine embryonic muscle development remains unclear. Here, we present a panorama view of circRNA expression in embryonic muscle development at 33-, 65-, and 90-days post-coitus (dpc) from Duroc pigs. An unbiased analysis reveals that more than 5,000 circRNAs specifically express in embryonic muscle development. The amount and complexity of circRNA expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 59 publications
(88 reference statements)
2
40
0
Order By: Relevance
“…Previous research has shown that circ-QKI and circ-BNC2 are upregulated during in vitro differentiation of control myoblasts, and downregulated in DMD conditions (Legnini et al, 2017). Many circRNAs have important biological functions by acting as microRNA or protein inhibitors ("sponges"), or are themselves translated during muscle development and growth (Legnini et al, 2017;Wei et al, 2017;Ouyang et al, 2018;Hong et al, 2019;Kristensen et al, 2019). CircLMO7, a circular RNA identified in bovine skeletal muscle at two developmental stages, was shown to regulate myoblast differentiation and survival by sponging miR-378a-3p (Wei et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that circ-QKI and circ-BNC2 are upregulated during in vitro differentiation of control myoblasts, and downregulated in DMD conditions (Legnini et al, 2017). Many circRNAs have important biological functions by acting as microRNA or protein inhibitors ("sponges"), or are themselves translated during muscle development and growth (Legnini et al, 2017;Wei et al, 2017;Ouyang et al, 2018;Hong et al, 2019;Kristensen et al, 2019). CircLMO7, a circular RNA identified in bovine skeletal muscle at two developmental stages, was shown to regulate myoblast differentiation and survival by sponging miR-378a-3p (Wei et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…While Liang et al (2017) profiled circRNAs in the postnatal pork muscle tissue, Hong et al (2019) analyzed circRNA expression profiles during embryonic skeletal muscle development in Duroc pigs. Their analysis used RNAse R-enriched samples harvested at 33, 65, and 90 days before birth (Hong et al, 2019).…”
Section: Swine -Meatmentioning
confidence: 99%
“…While Liang et al (2017) profiled circRNAs in the postnatal pork muscle tissue, Hong et al (2019) analyzed circRNA expression profiles during embryonic skeletal muscle development in Duroc pigs. Their analysis used RNAse R-enriched samples harvested at 33, 65, and 90 days before birth (Hong et al, 2019). Significantly fewer circRNAs were found to be expressed on day 90 when compared to the other two time points, an interesting find considering the main muscle fiber development in pigs occur at 33 and 65 days post-coitus, indicating circRNA may have crucial functions in the initiation stage of skeletal muscle development.…”
Section: Swine -Meatmentioning
confidence: 99%
“…At the cellular level, circRNAs are important regulators in many cellular processes, such as cell signaling [ 13 ], embryonic development [ 14 ], cellular senescence [ 15 ], and control of the cell cycle [ 16 ]. They also play critical roles in the occurrence and development of various types of diseases [ 17 ], including cardiovascular diseases (e.g., atherosclerotic vascular disease risk [ 18 , 19 ]), neurological disorders (e.g., Alzheimer’s disease [ 20 , 21 ]), osteoarthritis [ 22 ], diabetes [ 23 ] and, most importantly, in cancer [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%